Math, asked by variksh, 5 months ago

find the sum of expression given below
2a-3b,4a+6b+a+b

Answers

Answered by advay2608
3

Answer:

7a-4b is the answer I guess

Answered by s1046bimba22894
0

Answer:

2a+3b+4c

Step-by-step explanation:

It is instructed to subtract (2a−3b+4c) from the sum of (a+3b−4c),(4a−b+9c) and (−2b+3c−a).

So, First we will do the sum of the three given polynomials,

Sum =(a+3b−4c)+(4a−b+9c)+(−2b+3c−a)

=(a+4a−a)+(3b−b−2b)+(−4c+9c+3c)

=4a+8c

Now, we can perform the subtraction,

∴ Required difference

=(4a+8c)−(2a−3b+4c)

=4a+8c−2a+3b−4c

=2a+3b+4c

Similar questions